2017
DOI: 10.11648/j.ebm.20170304.11
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence on the J-Curve Between Pakistan and Selected South Asian Trade Partners

Abstract: Abstract:The earlier researches investigated the J-curve hypothesis along with the Marshall-Lerner condition in Pakistan used the OLS, 2SLS, 3SLS, and Instrumental Variables (IV) techniques. The estimates obtained from these studies may suffer from spurious regression problems as the models were estimated without incorporating the co-integrating property of the variables. Hence, the objective of this work is to analyze the trade balance model using relatively the new co-integration approach, the ARDL model. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Hence, the study confirmed having no evidence for J-curve phenomenon. Khalid (2017) found the same results in testing the J-curve phenomenon in Pakistan's trade with its main South Asian trading partners. Baek et al (2009) assessed the dynamic effects of exchange rate variability on agricultural bilateral trade of the United States with its major trade partners.…”
Section: The Relationship Between Exchange Rate Changes and The Tradesupporting
confidence: 55%
See 3 more Smart Citations
“…Hence, the study confirmed having no evidence for J-curve phenomenon. Khalid (2017) found the same results in testing the J-curve phenomenon in Pakistan's trade with its main South Asian trading partners. Baek et al (2009) assessed the dynamic effects of exchange rate variability on agricultural bilateral trade of the United States with its major trade partners.…”
Section: The Relationship Between Exchange Rate Changes and The Tradesupporting
confidence: 55%
“…The same source was used to obtain the exchange rate of the Egyptian pound against the currencies of the other partners. The same TB model estimated in several researches (Baek et al, 2009;Bahmani-Oskooee and Ratha 2004;Khalid, 2017) is used. The long-term model takes the following form:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found an evidence of short run asymmetric effect in almost all 11 industries but the short run effect transformed into a long run effect in only seven industries. Khalid (2017) examined the J-curve phenomenon between Pakistan and her selected south Asian trade partners using the annual time series data over the period 1975-2013 using ARDL approach. The author concluded that in case of Pakistan the j-curve phenomenon is rejected with its trading partners.…”
Section: Literature Reviewmentioning
confidence: 99%